Tales of the shimmering sky - Milord, Susan; Kitchel, JoAnn E. (Charlotte, Vt. : Williamson Pub., 1996)
Presents folktales, background information, and activities related to beliefs of peoples around the world about heavenly bodies, the seasons, and the weather.
The division of day and night -- The twelve months -- The hare in the moon -- The moon in safekeeping -- Great bear -- The boastful star -- The whriling wind -- The return of the clouds -- After the rain -- The theft of Thor's hammer.
Ten global folktales with activities
890L
Keywords: Astronomy -- Folklore; Weather -- Folklore; Folklore -- Juvenile literature; Tales; Seasons -- Folklore; Folklore